Allocation strategy of nonstructural carbohydrates in Spiraea L. across different grassland types in the Altai Mountains - Xuexi Ma; Xuexi Ma; Xuexi Ma; Xuexi Ma; Lianlian Fan; Lianlian Fan; Lianlian Fan; Meiniu Yang; Meiniu Yang; Jiangyue Li; Jiangyue Li; Meng Yan; et al. (Frontiers in Plant Science)
Global climate change and overgrazing have exacerbated shrub encroachment in arid and semi-arid grasslands and risking the stability and multifunctionality of grassland ecosystems. This shift between shrub and grassland raises a great concern to explicitly analyze the distribution of shrubs into arid and semi-arid grasslands and related environmental adaptation by using their nonstructural carbohydrates (NSCs) concentrations, and assess their allocation strategies and key determinants of these strategies. This research study was conducted in the Altai mountains of northwest of China and specifically focused on Spiraea, a dominant shrub in this region, and analyzed the NSCs component concentrations and their allocation in Spiraea leaves across different grassland types. The results showed significant variations in the NSCs concentrations, components, and allocation in Spiraea leaves across various grassland types, demonstrating higher overall values in meadows rather than grasslands (p < 0.05). Moreover, the total NSCs concentrations(the sum of soluble sugar and starch concentrations, and the ratio of soluble sugar to starch) exhibited consistent responses to environmental changes, and indicated increasing trends with elevation, soil water content (SWC), and soil total nitrogen concentrations (TN), while decreasing with mean annual temperature (MAT). Notably, MAT and SWC were emerged as the factors with the highest influence on NSCs concentrations and allocation in Spiraea leaves. These findings indicate that Spiraea in the Altai mountains can rapidly adapt to environmental changes across different grassland types by calibrating their NSCs concentrations and composition. These findings also present an insightful theoretical foundation for managing shrub-grassland encroachments in the Altai mountains region and other arid and semi-arid regions.